Molecular Identification of Yeasts Isolated from Dadih by RFLP-PCR and Assessment on Their Ability in Utilizing Lactate - YOGA DWI JATMIKO; MIGUEL DE BARROS LOPES; MARY D BARTON (Indonesian Society for microbiology, 2012)
A wide variety of yeasts have been involved in traditional fermented foods, and potentially contributed to the development of product properties. The existence of indigenous yeasts in dadih, a traditionally fermented form of buffalo milk of West Sumatera, has been reported but an accurate identification is still required to be conducted. This study was aimed to identify yeasts isolated from dadih using a molecular approach, and to evaluate their lactate utilization. A total of 51 isolates were characterized and identified as Pichia jadinii and Candida stellimalicola using PCR amplification of the 5.8S - internal transcribed spacer region combined with restriction fragment length polymorphism (RFLP) analyses and gene sequencing. The former species were the dominant one in this tested product. Their ability to utilize lactate was demonstrated, indicating that they could modify the sensory characteristics of dadih, and hence interact with the indigenous lactic acid bacteria in dadih. The restriction profiles of the dadih yeasts can be used as a data base for rapid identification of yeasts in the future. Further work is still needed to elucidate the dadih yeast ecology.